Sustainable Housing for Malaysian: A Crowdfunding Initiative through SEM Perspective - Khairul Adlee, Nurul Faziera; Misiran, Masnita; Md Yusof, Zahayu; Sapiri, Hasimah; Amit, Norani (2021)
Crowdfunding has risen as a progressive financing model that enables small businesses to raise fund. In Malaysia, this platform is being innovated into real estate crowdfunding initiative, to ease current restriction of home ownership among category of people that is otherwise difficult to secure mortgages from conventional platform. Therefore, this paper examines the perception of Malaysian young adults towards property crowdfunding platform using structural equation modelling. The aim is to determine the perceptions of the targeted group towards this investment vehicle. Results showed that the expectation on return and saving portrayed the highest relationship, indicating highest effects towards the perception of property crowdfunding among young adults. While relationship between the return expectation and risk tolerancy showed no effects towards the perception of property crowdfunding. This initiative has potential to become the driver for sustainable development, as the risk of faults in paying mortgage can be reduced significantly compared to traditional means